Lost urine means lower yields - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
The trend to zero-grazing and intensive livestock production has important implications for the cycling of nutrients: it is leading to crop land being denied valuable urine. Under many traditional systems in sub-Saharan Africa, livestock graze crop...